Model for Public-Private Partnership in the Tax-Free Setup - Młodkowski, Paweł; Tastulekov, Serikzhan (Wydawnictwo Uniwersytetu Rzeszowskiego, 2015)
The concept of public-private partnership as a vehicle for arranging provision of public goods or achieving socially desirable public policy goals has a long history and multitude of studies. This paper offers a simple, but crucial modification of the basic model of the public-private partnership financing by Engel, Fisher and Galetovic (2007). Due to growing popularity of PPP in creating and operating infrastructure in resource-based economies, our innovation is intended to adjust the model setup to specific public finance conditions. It happens that in case of many resource-based economies the central government operates in favorable conditions. Budgets in oil&gas exporting countries do not face any constraints on public spending. This is sometimes associated with a tax-free system of public finance. As a consequence, models for optimizing social welfare by benevolent, riskneutral planner with taxes and cost of public funds do not match the actual situation in countries we wish to focus on. The choice for the government, when PPP is considered is simple. Decision concerns the scale of subsidy. While the subsidy is not financed with distortionary taxation, the cost of public funds is different from what we find in available formulations of models. Therefore, in our paper we discuss the specific features of tax-free, resource-based economies and we modify the original model by Engel, Fisher and Galetovic (2007) to arrive at a formulation more appropriate for Arab countries, or other, where distortionary taxation does not exist. The main findings and conclusions are as follows: (1) without taxes there are no negative externalities of financing subsidies to support PPP, (2) some of the benefits of the PPP are not present without distortionary taxation.

Idea partnerstwa publiczno-prywatnego, jako sposobu na dostarczanie dóbr publicznych lub osiąganie społecznie pożądanych celów polityki posiada już długą historię i liczne studia literaturowe. Niniejszy artykuł oferuje drobną modyfikację podstawowego modelu finansowania partnerstwa publiczno-prywatnego (PPP), stworzonego pierwotnie przez Engela, Fishera i Galetovica (2007). Ze względu na rosnącą popularność PPP w tworzeniu i użytkowaniu infrastruktury w gospodarkach opartych na wydobyciu surowców naturalnych nasza innowacja w modelu ma na celu dopasowanie ram modelu do specyficznych warunków sektora finansów publicznych w tych właśnie krajach. Okazuje się, że w wielu gospodarkach opartych na wydobyciu surowców sektor publiczny funkcjonuje w sprzyjających warunkach. Budżet centralny w krajach naftowych nie posiada tradycyjnie pojmowanych ograniczeń dla wydatków publicznych. Jest to jednocześnie połączone z brakiem jakichkolwiek podatków. W konsekwencji, modele optymalizacyjne dla dobrobytu społecznego z punktu widzenia dobroczynnego, neutralnego wobec ryzyka planisty centralnego w warunkach z podatkami nie odpowiadają faktycznej sytuacji w krajach bezpodatkowych. Właśnie dla tego przypadku oferujemy nasze rozwiązanie. Wybór, przed którym stoi rząd, gdy rozważane jest partnerstwo publiczno-prywatne jest prosty. Decyzja dotyczy subsydiowania. Jeśli subsydia nie są finansowane z podatków, koszt funduszy publicznych rożni się od tego, co znajdujemy w dostępnych modelach. Z tego powodu, w naszym artykule prezentujemy specyficzne cechy gospodarek opartych na wydobyciu surowców, w których brak podatków i oferujemy modyfikację oryginalnego modelu stworzonego przez Engela, Fishera i Galetovica [2007] pozwalającą na uchwycenie cech charakterystycznych dla krajów naftowych lub innych, w których nie istnieją podatki. Główne wnioski to: bez podatków nie występują negatywne koszty zewnętrzne z tytułu finansowania subsydiami projektów infrastrukturalnych w formie PPP, (2) niektóre z korzyści wskazywanych w przypadku PPP nie występują, gdy brak jest podatków.
Keywords: public-private partnership; resource-based economy; public policy; tax-free system; partnerstwo publiczno-prywatne; polityka publiczna; subsydia; system bezpodatkowy; podatki